Intravenous thrombolysis for pure pontine infarcts caused by cardiac myxoma: a case report and literature review. (2nd June 2020) - Dong, Mingming; Ge, Yusong; Li, Jinwei; Fu, Kailei; Zhang, Liyang; Teng, Weiyu; Tian, Li
Abstract: Purpose: Cardiac myxoma (CM) is a rare but important cause of ischemic stroke, and typically involves the middle cerebral artery and rarely affects the brainstem only. The safety and efficacy of intravenous thrombolysis (IVT) for CM-related acute cerebral embolism are not clear. Methods: We report a case of a 55-year-old woman who suffered a CM-related acute cerebral embolism presented with pure pontine infarcts and achieved a favorable prognosis by IVT with urokinase. We summarized the clinical data of this entity and performed a literature review of 21 previous reports of patients with CM-related acute cerebral embolism who were treated with IVT. Results: In combination with previous reports, we found that the majority of patients (81.8%) obtained improvements in symptoms after IVT, including 63.6% in remarkable clinical improvement. The total rate of IVT-induced intracerebral hemorrhage was 22.7% and all occurred within 36 h, including hemorrhagic infarction type 1 (4.5%) and parenchymal hematoma type 2 (18.2%). Most of the cases had relatively good outcomes and no case died due to IVT. Conclusion: Taken together, our findings support the use of IVT as an effective and safe tool for the ultra-early treatment of CM-related acute phase ischemic stroke.